Fluidized Bed Drying of Ginger Flakes - Singh, K K; Tiroutchelvame, D; Patel, S (Journal of Agricultural Engineering, 2008)
Drying of ginger (Zingiber officinale) flakes was studied under fluidized bed conditions in the temperature range of 50 to 80degree C and pretreatment of calcium oxide in the range of 1 to 2.5%. Drying rate at 60degree C air temperature decreased from 0.43 to 0.17 gls with the change in moisture content from 300 to 10% d.b. The volatile oil in dried flakes decreased from 1.2 to 0.99% with increase in drying temperature from 50 to 80degree C. The effect of drying temperature and concentration of calcium oxide on colour L*(lightness) value and drying ratio was non-significant at P&gt0.05, however, these had significant effect on rehydration ratio.